Explaining the Role of Consultation and Negotiation on the Life of Imam Ali in Spite of Having Divine Knowledge and Infallibility - Aronaghi, Abasali; Asadbeigi, Ardashir; Baghestani Kozehgar, Mohammad; Khajehmirza, Mahmoud (Journal of History Culture and Art Research, 2017)
Consultation and negotiation is one of the aspects of human life that provide the ground of using the experience and knowledge of others, the point that infallibles have divine knowledge provided the ground for some to deny and dispute this certain principle of life, and assume that because of God’s protection, the infallibles are safe against any wrong doing and sin, consultation and negotiation is meaningless and they do not need it. This study is trying to remove this ambiguity of explaining the situation and reason of consultation in a pattern of life that in spite of having divine knowledge and infallibility has a valuable position and is shown in his action and speech. Consultation and negotiation have significant participation in different areas of the life of Imam Ali, including individual, social, and political areas. In addition to considering the consultation particularly the features of consultants and consulting areas, the dos and don’ts were cleared, to draw enormous benefits consulting, drawing people’s attention to the council principle, not being guilty of despotism, characterizing the followers and flourishing their talent, showing mercy and affection hearts and patterning the posterity, he was negotiating and consulting.